Features of the iSCSI protocol. - Meth, K.Z.
The iSCSI protocol specifies how to access SCSI storage devices over a TCP network. In this article we give a brief introduction to the iSCSI protocol and a brief comparison with alternative technologies. We then discuss the basic features of the iSCSI protocol: sessions, naming, discovery, security, data placement, and recovery.
Keywords: SCSI storage devices; TCP network; Data placement; Discovery; iSCSI protocol; Naming; Recovery; Security; Sessions